MEMBRANE-SАVING ACTION OF TRIMETAZIDINE IN SUBJECTS WITH ACUTE MYOCARDIAL INFARCTION - S. V. Vasilyev; E. Yu. Maychuk; V. Yu. Vasilyev (Российский кардиологический журнал)
The article concerns the assessment of functional condition of cell membranes in a variety of pathological conditions, influence of various physical and chemical factors and pharmacological drugs. Aim. To reveal cytoprotection action of trimetazidine in shortand longterm periods of acute myocardial infarction. Material and methods. As controls we used the condition of cell membranes under the age aspects in healthy volunteers (n=106). Into main group we included patients with acute myocardial infarction (n=46), of those to 25 we added trimetazidine to the standard treatment. We studied the level of membrane damage and cytoprotective action of trimetazidine at different stages of treatment by exposure cell membranes to electricity. Results. Inclusion of trimetazidine to MI treatment allows to reduce by 2 days the period of functional membrane condition restoration, that had kept for up to 3 months of observation. Conclusion. Improvement of erythrocyte membranes condition and general condition of patients after acute MI is significantly proved by addition of cytoprotector trimetazidine to the treatment complex.